Welfare implication of liberalization policy option for rice sector in Malaysia - Umar, Haruna Suleiman (2015)
Rice sector in Malaysia is heavily supported and protected because of its socio-political and economic importance. These supports provided in form of production subsidy and import restriction intended to improve farmers’ income through cut in production cost, attaining self-sufficiency level and rice-food security. However, the country membership in the World Trade Organization (WTO) and ASEAN Free Trade Area (AFTA) makes it mandatory to open up the sector in terms of adopting market-driven policy and by extension exit all forms of supports enjoy in the sector. The government efforts to have a trade-off between the two opposing policies depend on the knowledge of welfare impact of such policy option on the society at large. Hence, the study is designed to estimate welfare implications of complete liberalization policy in the rice sector. Specifically, the study is designed to achieve the following objectives: (i) estimate supply and demand models for Malaysian rice market; (ii) simulate the effects of alternative rice sector policy on the national output, paddy producer price, rice retail price, rice consumption level and import quantity; and, (iii) determine welfare implications of the policy options. Time series data (1980-2012) were collected and analyzed using appropriate time series econometric models: ARDL, ECM and OLS Multiple Regression. This estimation preceded the specification of structural equations by disaggregation of the supply-side of the sector into All-season, Main-season and Off-season paddy productions; while demand side is represented by aggregated single demand equation. Estimated coefficients were subjected to and pass the relevant diagnostic tests. The estimated elasticities were used for scenarios simulation and forecast. The results generated were further used in estimating the society welfare changed through appropriate estimation techniques. The results show that paddy area planted did not respond significantly to an increase in paddy producer price. Yield response significantly to technological trend but insignificantly to fertilizer subsidy. Rice consumption per capita is unresponsive to retail price movement. Rice consumption in relation to an increase in income signifies inferior good in the long-run but normal good in the short-run basis. Wheat is a substitute to rice in consumption. The complete liberalization of rice sector would witness the following situations by the year 2020: rice domestic production would decline by 9.7%; paddy Farm price would decrease by 2%; rice retail price decrease by 7.6%, rice total consumption increase by 0.1% and rice import would rise by 19.4%. The policy would result in paddy producer welfare loss of RM87M, consumer welfare gain of RM 829M while the sum of RM1B would be saved as revenue. Societal welfare gain is about RM 950M. These results would serve as empirical guide in aiding policy makers toward decision to adopt market driven policy since society as a whole would be better-off as net gain far outweigh the welfare loss. This would lead ultimately to general welfare improvement in the society at large.